Kajian Literatur Tentang Penerapan Model Pembelajaran Problem Based Learning (PBL) pada Materi Satuan Waktu Mata Pelajaran Matematika Kelas III SD - Wibiyanti, Annisa Delvira Putri; Noerdianasari, Miranda; Setiyawan, Hery (Indo-MathEdu Intellectuals Journal, 2025)
This literature review aims to determine the application of the Problem Based Learning (PBL) learning model on the material of time units in mathematics subjects for grade III of elementary school. The background of this literature review is the low understanding of students towards the concept of time units and the minimal participation of students in the learning process. This study uses a qualitative approach with a classroom action method carried out in two cycles. Data collected through student and teacher activities as well as learning outcome tests are analyzed descriptively. The results of the literature review show that the application of the Problem Based Learning (PBL) learning model can improve understanding of the concept of time units, active student participation in discussions, and students' ability to solve problems on time unit material. Thus, the Problem Based Learning (PBL) learning model is effective for improving the quality of mathematics learning in elementary schools, especially on time unit material.